Debating Ethical Research with Human Subjects - Roulston, Kathryn; Preissle, Judith (Acta Paedagogica Vilnensia, 2018)
[full article in English]Drawing on our experience serving on an ethics review board in the United States, two scholars present three fictionalized examples to illustrate three issues in reviewing research proposals for the protection of human subjects. These are (1) the impetus for the creation of new knowledge on topics of significance, especially involving those considered to be vulnerable participants, (2) balancing the needs of novice and experienced researchers to design studies that contribute to their fields of interest while protecting the interests of participants and (3) disagreements among board members on the requirements for responsible conduct of research. Recommendations are provided for ethical review to the faculty who supervise student research as well as new scholars submitting proposals for ethical review.
Keywords: research ethics; human subjects protection; ethics review committees; Institutional Review Boards